Anthropometric indices and clinical assessment of nutrition score (CAN Score) in detection of fetal malnutrition at birth - Dr. Abhishek Kumar Tiwari; Dr. Debashish Bandyopadhyay; Dr. Bijan Saha (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Low birth weight is commonly used criterion for identifying fetal malnutrition. But fetal malnutrition may be present at any birth weight and it is important to recognize it due to its high incidence of morbidity and mortality. Hence, CAN score has been introduced as the gold standard tool for identification of fetal malnutrition.Objectives: 1) To compare the assessment of nutritional status using anthropometric indices and CAN score and assess their accuracy. 2) To develop a screening tool in identifying fetal malnutrition using anthropometric indices.Methods: This prospective observational study included 349, term, live born, singleton newborns with no major congenital malformation. Nutritional status assessment was done on the basis of CAN score within 24 hours of birth. Ponderal Index (PI), Body Mass Index (BMI) and mid-arm to head circumference ratio was calculated and compared with CAN score.Results: Incidence of fetal malnutrition was 20.1%. Newborns identified as malnourished by PI, BMI, MAC/HC were compared with CAN score. BMI had the highest sensitivity (75.7, p<0.001) and combined with PI sensitivity increased to 89.1%.Conclusion: BMI is the best screening tool for malnutrition and coupled with PI makes it a good indicator of normal nutrition.